Isolation of the Fungus on Mantis shrimp (Squilla mantis) Trafficked at the Fish Quarantine Station for Quality Control of Fishery Products Safety (SKIPM) Pekanbaru - Anggi Rohita; Feli Feliatra; Dini Suwandari (Tropical Marine Enviromental Sciences, 2022)
Mantis shrimp as one of the foods that come from the sea and ponds is not immune from disease infection, one of which is infection by fungi. Mantis shrimp (Squilla mantis) is one of the crustaceans that has a physical shape resembling a praying mantis. This research was conducted on January– February, 2022 at the Fish Quarantine Station for Quality Control and Safety of Fishery Products (SKIPM) Pekanbaru, Riau. The research method used is the survey method. Mantis shrimp samples came from Bengkalis which were trafficked at SKIPM Pekanbaru. The results of the incubation in the first isolation stage that have been overgrown with fungi, then the purification stage is carried out. The fungus that grows is carried out in the staining stage to make it easier to observe the fungus under a microscope. Furthermore, the identification of fungi in mantis shrimp using a microscope and referring to the book Identifying Filamentous Fungi. The results showed that there were 2 types of fungi, namely Fusarium sp. and Penicillium sp